"At Gethsemane": The Shandong Decision at the Paris Peace Conference and Wilson's identity crisis. Issue 1 (2nd January 2021) - Jianbiao, Ma
Abstract: U.S. President Woodrow Wilson's proposed policy of Wilsonianism during World War I was riddled with inherent contradictions. Wilson wanted to resolve the conflicts between imperialist powers and their colonial populations through the principle of "national self-determination, " but also relied on the support of the victorious great powers to realize his vision for a League of Nations. The first goal put him at odds with the great powers while the latter required him to ally with them. Wilson's contradictory relationship with the victorious Allies manifested itself in the resolution of the Shandong question and how Wilson was unable to reconcile the moral principle of self-determination with realist power politics. To form a League of Nations, Wilson had to choose between "ethics" and "politics, " leading to a personal identity crisis. For Wilson, choosing to trust in collective security over moral responsibility was a choice made "at Gethsemane."